PWE-006 Differential immune responses between proximal and distal colorectal cancer. (17th June 2017) - Al-Hassi, HO; Lee, GH; Murugananthan, A; Malietzis, G; Mann, ER; Landy, J; Ng, O; Acheson, A; Bernardo, D; Brookes, MJ; Knight, SC
Abstract : Introduction: Colorectal cancer (CRC) is a major cause of mortality. Dendritic cells (DC) promote tumour immunity or tolerance dictated by tissue microenvironment. Proximal colon (right-sided) CRC has lower incidence but poorer prognosis than distal colon (left-sided) CRC. This may be due to immunological differences between the proximal and distal colon. However, cellular and molecular studies on these differences especially in CRC are scarce. We aimed to characterise the immune activity in both compartments. Method: Activation and migration of DC from human mucosal and tumour biopsies in health and CRC were investigated using flow-cytometry, immunohistology. Functional studies were performed using migration assay techniques. E-Cadherin, a tumour dissemination inhibitor was determined by real time PCR in a separate group of tumours from anaemic CRC patient. Results: Co-stimulatory molecules (CD40/CD86) were expressed on more DC from proximal than distal colon in health and CRC (p=0.03; p=0.01 respectively). In CRC, DC from proximal mucosa and tumour showed increased skin-homing (CLA) and ILT3 (marker for immature DC) indicating reduced potential to focus immune activity to this compartment (p=0.03; p=0.01 respectively). CRC-DC showed increased CCR7 (lymph node homing) with greater migration but with negative correlation with tumour size. E-Cadherin mRNA fold-change was significantly lower on proximal tumour cells compared with those in the distal compartment. Functional studies using supernatants from normal mucosae or tumours reproduced the above changes in CRC-DC; changes thus reflected changed gut micro-environment in CRC. Conclusion: Higher immune activity, in proximal colon, may underlie lower tumour incidence but higher tumour aggression due to tumour evolution in immunologically active microenvironment. This may have an impact on colorectal cancer treatment, for example, optimisation of current therapies based on the anatomical site of the colorectal tumour. Hence, establishment of standardised management for colon cancer by tumour location is needed. Reference: . Bernardo D, et al., Chemokine (C-C Motif) Receptor2 Mediates Dendritic Cell Recruitment to the Human Colon but Is Not Responsible for Differences Observed in Dendritic Cell Subsets, Phenotype, and Function Between the Proximal and Distal Colon. Cell Mol Gastroenterol Hepatol 2016;2(1):22–39. Disclosure of Interest: None Declared